Optimising the Use of Backyard Land to Build the Socio-Economic Resilience of the Community in Gunungsari Village, West Lombok Regency - M Yamin; A. Wahab Jufri; Kheruddin; I Wayan Mertha; Ade Andriyan (Unram Journal of Community Service, 2026)
Limited access to economic resources and high levels of social vulnerability among rural communities necessitate empowerment strategies focused on the sustainable utilisation of local potential. This community service initiative is designed to optimise the use of backyard land as a means of strengthening the socio-economic resilience of the community in Gunungsari Village, West Lombok Regency. The programme is also aimed at supporting the fulfilment of nutritional needs and increasing household income, whilst simultaneously enhancing aesthetic value through the creation of a pleasant, cool, healthy and comfortable environment, and contributing as a means of physical activity to improve fitness and physical resilience. The programme is implemented using a participatory approach comprising the stages of needs identification, extension, technical cultivation training, mentoring, and sustainability evaluation. This activity involves 16 participants from the local community, supported by four lecturers from the Biology Education Study Programme at the Faculty of Teacher Training and Education, Mataram University. The crops developed include Capsicum annuum, Solanum melongena, Amaranthus sp., and Ocimum sp., utilising vertical farming models, pot cultivation, raised bed systems, and integrated fish farming through the rearing of catfish in buckets (budikdamber). The results of the implementation demonstrated an increase in participants’ knowledge and skills in the integrated management of crop and fish cultivation. The optimisation of backyards contributes to improved household food availability and opens up additional income opportunities. Socially, this activity promotes the strengthening of interaction, collaboration, and collective awareness within the community regarding the urgency of family-based food security as the foundation for sustainable socio-economic development.